2015
DOI: 10.1371/journal.pone.0124248
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the AcrAB Components of the AcrAB-TolC Multidrug Efflux Pump of Yersinia enterocolitica Is Subject to Dual Regulation by OmpR

Abstract: OmpR is a transcriptional regulator implicated in the control of various cellular processes and functions in Enterobacteriaceae. This study was undertaken to identify genes comprising the OmpR regulon in the human gastrointestinal pathogen Yersinia enterocolitica. Derivatives of an ompR-negative strain with random transposon insertions creating transcriptional fusions with the reporter gene lacZ were isolated. These were supplied with the wild-type ompR allele in trans and then screened for OmpR-dependent chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 60 publications
0
21
1
1
Order By: Relevance
“…These results corroborate the recent finding in Salmonella that an increase in KdgM proteins in a mutant strain lacking elongation factor P leads to increased OM permeability (Zou et al, 2011 ). However, contrary to the Salmonella data we were unable to demonstrate increased susceptibility to the gentamicin, probably due to the presence of a functional AcrAB efflux system in Y. enterocolitica (Raczkowska et al, 2015 ). Interestingly, the increased permeability of Y. enterocolitica membranes caused by overexpressed KdgM2 was only observed at 37°C and not at the normal growth temperature of 26°C.…”
Section: Discussioncontrasting
confidence: 97%
“…These results corroborate the recent finding in Salmonella that an increase in KdgM proteins in a mutant strain lacking elongation factor P leads to increased OM permeability (Zou et al, 2011 ). However, contrary to the Salmonella data we were unable to demonstrate increased susceptibility to the gentamicin, probably due to the presence of a functional AcrAB efflux system in Y. enterocolitica (Raczkowska et al, 2015 ). Interestingly, the increased permeability of Y. enterocolitica membranes caused by overexpressed KdgM2 was only observed at 37°C and not at the normal growth temperature of 26°C.…”
Section: Discussioncontrasting
confidence: 97%
“…The consensus OmpR ‐binding site of Y ersinia spp. and logo motif defined based on experimentally validated OmpR ‐binding elements present in the promoter regions of inv (Brzostek et al ., ), flh DC (Hu et al ., ; Raczkowska et al ., ), acr R and acr AB (Raczkowska et al ., ), and omp C , omp F , omp R and omp X (Gao et al ., ). W eb L ogo (http://weblogo.berkeley.edu/logo.cgi) was used to obtain consensus sequence logos in which the height of individual letters within the stack of letters represents the relative frequency of that particular nucleotide at a given position, and the number of letters in the stack indicates the degree of conservation at that position.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to E. coli, we found that the OmpR of Y. enterocolitica is involved in the positive control of flagellum synthesis and motility (Raczkowska et al, 2011). OmpR-dependent regulation of the components of the Y. enterocolitica multidrug efflux pump AcrAB-TolC was also demonstrated (Raczkowska et al, 2015). Another study showed that an ompR mutant of Y. enterocolitica strain Ye9N exhibits a reduced ability to survive under acidic conditions in vitro and within macrophages, which indicates that OmpR is involved in the adaptation of this bacterium to low pH (Brzostek et al, 2003).…”
Section: Introductionmentioning
confidence: 68%
“…The high-level pathogenic strain 8081, isolated in the United States, is the most studied Y. enterocolitica strain with respect to its virulence factors and their contribution to pathogenesis in mammals (Portnoy et al, 1981). The low-level pathogenic strain Ye9N (bio-serotype 2/O:9), isolated in Poland, has been the research object of many studies, especially concerning the role of OmpR in regulating the virulence properties and adaptive abilities of Y. enterocolitica (Brzostek et al, 2003(Brzostek et al, , 2007Raczkowska et al, 2011Raczkowska et al, , 2015Skorek et al, 2013;Nieckarz et al, 2016Nieckarz et al, , 2017.…”
Section: Discussionmentioning
confidence: 99%